Experimental investigations on light weight sandwich panels under flexural loading - Ganapathi, S. Chitra; Peter, J. Annie; Iyer, Nagesh R.; Lakshmanan, N. (Journal of Structural Engineering, 2024)
In civil engineering, reinforced concrete sandwich panels are generally considered as the high performance composite load bearing building elements, which can be used as floors, walls and roofs in residential and medium rise commercial buildings. This paper presents the details of studies conducted on innovative light weight concrete sandwich panels, which are composed of light weight insulating material as inner core surrounded by high strength reinforced concrete skins on all sides. Extensive research study is carried out on flexural behavior of light weight concrete sandwich panels of size with two different solidity ratios viz. p1-3x1.2x0.1m and p2-3x1.2x0.15m. The study includes load deflection profile, strain variation in the rebars and concrete skin across the panel depth and the mode of failure pattern. From the experimental studies it is observed that the flexural strength is generally increased by about 44% and the stiffness by about five folds for the least solidity ratio case. Thus, from the experimentally obtained strain values at top and bottom of concrete skin and from the mid rod of the panel, the strain variation and strain discontinuity across the depth are linear and very nominal, which shows the integral behavior of the sandwich panel. This demonstrates the accomplishment of full shear transfer between the wythes. Also from the measured strains of the shear connectors, it is observed that the legs of the truss connectors absorbed small strains during the load transfer from the upper to lower wythe, which indicates 100 % shear transfer between the wythes. In all solidity ratio case panels, the habitual one way flexural cracking pattern is exhibited in the bottom wythe along the width of the panel. The first crack / yielding occurred approximately at a load of 30% of the ultimate load, which shows the large ductility characteristics of the panels. The panels in turn proved fully composite, very ductile and consuming large deformation prior to failure. Based on the responses of the experimental study, it is inferred that the light weight concrete sandwich panels behave structurally in a very similar manner to reinforced concrete panels.